Poly‐GP in cerebrospinal fluid links C9orf72‐associated dipeptide repeat expression to the asymptomatic phase of ALS/FTD - Carina Lehmer; Patrick Oeckl; Jochen H Weishaupt; Alexander E Volk; Janine Diehl‐Schmid; Matthias L Schroeter; Martin Lauer; Johannes Kornhuber; Johannes Levin; Klaus Fassbender; Bernhard Landwehrmeyer; German Consortium for Frontotemporal Lobar Degeneration; et al. (EMBO Molecular Medicine)
Abstract The C9orf72 GGGGCC repeat expansion is a major cause of amyotrophic lateral sclerosis and frontotemporal dementia (c9ALS/FTD). Non‐conventional repeat translation results in five dipeptide repeat proteins (DPRs), but their clinical utility, overall significance, and temporal course in the pathogenesis of c9ALS/FTD are unclear, although animal models support a gain‐of‐function mechanism. Here, we established a poly‐GP immunoassay from cerebrospinal fluid (CSF) to identify and characterize C9orf72 patients. Significant poly‐GP levels were already detectable in asymptomatic C9orf72 mutation carriers compared to healthy controls and patients with other neurodegenerative diseases. The poly‐GP levels in asymptomatic carriers were similar to symptomatic c9ALS/FTD cases. Poly‐GP levels were not correlated with disease onset, clinical scores, and CSF levels of neurofilaments as a marker for axonal damage. Poly‐GP determination in CSF revealed a C9orf72 mutation carrier in our cohort and may thus be used as a diagnostic marker in addition to genetic testing to screen patients. Presymptomatic expression of poly‐GP and likely other DPR species may contribute to disease onset and thus represents an alluring therapeutic target.